Exosomes from MDA-MB-231 cell line induce apoptosis gene expression, and phenotype and functional changes in Dendritic Cells: Possible role of Caspase-9 gene and pro-apoptotic miRNAs - Oliveira, Brenda Raissa de (2021)
Fundação de Amparo à Pesquisa do Estado de Minas Gerais (FAPEMIG)